SOCIAL MEDIA PROMOTIONS –CAN WE RESTRICT IT UNDER LAWS? - Chaturvedi, Sumit; Gupta, Sachin (International Journal of Research -GRANTHAALAYAH, 2014)
Social Media, today, is the best way for companies for connecting with their prospective consumers. Social media is the medium to mix with people. These new media prevail the trust of consumers by connecting with them at a higher level. Social media marketing is the new mantra for several brands from few years. Marketers are taking note of many different social media opportunities and commencement to implement new social initiatives at a higher rate than ever before. Social media marketing and the businesses that make use of it have become more primitive. One cannot afford to have no existence on the social channels if the competitor is making waves with its products and services. The detonation of social media phenomenon is as mind boggling as that and the pace at which it is growing is infuriating. International companies have recognized social media Promotions as a latent marketing platform utilized them with innovations to power their advertising campaign with social media marketing. Social media is used for Promotions of various things .at certain points it is a very good medium to promote the things but in dark side it is misused .Here the question arises that can we restrict it under laws? Can we control these things? What are the things which we can keep in mind and through which we can try to avoid its effect. This paper is an attempt to enlighten these things.